STUDENT ACTIVITIES IN THE QUANTUM TEACHING LEARNING MODEL ON GEOMETRY MATERIAL AT SMPIT AL-FITYAN SCHOOL ACEH - Muhammad Yani; Afdhalil Ilyas; Siti Raudhah Maidari (Jurnal Ilmiah Pendidikan dan Pembelajaran Matematika, 2024)
The Quantum Teaching learning model is one of the learning models that is able to condition students to learn actively with the TANDUR steps in it. This study aims to determine student activities during learning with the Quantum Teaching learning model on geometry material in class VIII-C SMPIT Al-Fityan School Aceh. This study uses a qualitative approach with a descriptive research type. The subjects in this study were 26 students of class VIII-C SMPIT Al-Fityan School Aceh. The instruments in this study were the Learning Implementation Plan (RPP), Student Worksheets (LKPD), and Student Activity Observation Sheets (LOAS). Furthermore, the data obtained from the results of observations of student activities during the learning activities were analyzed using percentages. The results of the study showed that student activities during the learning process through the application of the Quantum Teaching learning model on geometry material in class VIII-C SMPIT Al-Fityan were in the effective category, meaning that all students were active in learning as expected by the teacher. However, it is expected that teachers can still create dynamic learning conditions so that they can increase students' positive activeness in learning and teachers can also use music when implementing the Quantum Teaching learning model to organize moods, change students' mental states, and support the learning environment